Copper(II) Complexes with Carnosine Conjugates of Hyaluronic Acids at Different Dipeptide Loading Percentages Behave as Multiple SOD Mimics and Stimulate Nrf2 Translocation and Antioxidant Response in In Vitro Inflammatory Model - Francesco Bellia; Valeria Lanza; Irina Naletova; Barbara Tomasello; Valeria Ciaffaglione; Valentina Greco; Sebastiano Sciuto; Pietro Amico; Rosanna Inturri; Susanna Vaccaro; Tiziana Campagna; Francesco Attanasio; et al. (Antioxidants, 2023)
A series of copper(II) complexes with the formula [Cu2+Hy(x)Car%] varying the molecular weight (MW) of Hyaluronic acid (Hy, x = 200 or 700 kDa) conjugated with carnosine (Car) present at different loading were synthesized and characterized via different spectroscopic techniques. The metal complexes behaved as Cu, Zn-superoxide dismutase (SOD1) mimics and showed some of the most efficient reaction rate values produced using a synthetic and water-soluble copper(II)-based SOD mimic reported to date. The increase in the percentage of Car moieties parallels the enhancement of the I50 value determined via the indirect method of Fridovich. The presence of the non-functionalized Hy OH groups favors the scavenger activity of the copper(II) complexes with HyCar, recalling similar behavior previously found for the copper(II) complexes with Car conjugated using β-cyclodextrin or trehalose. In keeping with the new abilities of SOD1 to activate protective agents against oxidative stress in rheumatoid arthritis and osteoarthritis diseases, Cu2+ interaction with HyCar promotes the nuclear translocation of erythroid 2-related factor that regulates the expressions of target genes, including Heme-Oxigenase-1, thus stimulating an antioxidant response in osteoblasts subjected to an inflammatory/oxidative insult.